Diabetes educators’ competencies in facilitating self-management among diabetic patients at government health care centres in Malaysia: a concept paper - Subramaniam, Umma Devi; Kadir @ Shahar, Hayati; Ismail, Suriani; Gyanchand Rampal, Lekhraj Rampal (Community Health Society Malaysia, 2014)
Background: According to The Fourth Malaysian National Health Morbidity Survey (2011), 2.6 million adults of 18 years and above have diabetes mellitus. Diabetes education has been a major concern of the healthcare professionals. Diabetes Educators are health care providers who specialise in the provision of diabetes self-management education and care for people with diabetes. Diabetes self-management education is a speciality area of practice and is both a therapeutic and educational intervention. In Malaysia, the role of Diabetes Educators has been highlighted with the starting of post-basic Diabetes Management Course in 2000 by the Ministry of Health, Malaysian Diabetes Association and Universiti Malaya. The course was conducted by experts in the field of diabetes care. Since the year of 2003, the training was being conducted by the Training Division of Ministry of Health. The Diabetes Educators who are trained need to apply their knowledge and skills in diabetes management to provide self-management education to patients. The aim of the study is to determine Diabetes Educators’ competencies to facilitate self-management among diabetic patients in Government Healthcare Centres in Malaysia. The specific objectives of the study are to determine the socio-demographic factors of Diabetic Educators, their competencies on the five domains consisting of clinical understanding of diabetes management, culturally-competent supportive care across the lifespan, teaching and learning skills, diabetes self-management practices, and health promotion and other programs as well as the challenges faced by them in counselling diabetic patients. Other objectives are to identify the association between socio-demographic and socio-economic factors of Diabetes Educators with the five competencies studied. Materials and Methods: This is a cross-sectional study using a self-administered questionnaire adapted from American Association of Diabetes Educators Guidelines (2013) with 438 diabetes educators randomly selected using simple random sampling in five Government Primary and Secondary Healthcare Centres in Malaysia. The administration of the questionnaire will be done from October until November 2014. Descriptive analysis such as mean with standard deviation will be used to illustrate the five competencies of Diabetes Educators’ self-reported knowledge consisting of clinical understanding of diabetes management, culturally-competent supportive care across the lifespan, teaching and learning skills, diabetes self-management practices, and health promotion and other programs. The study will illustrate the challenges faced by them in carrying out their daily task. To test the differences in the mean scores for the independent variables (socio-demographic and socio economic factors), t-test and One Way Analysis of Variance (ANOVA) will be employed and the chi-square test will be used to find the association between the independent variables and dependent variables (five domains of competencies of diabetes educators). Expected result: The result of the study will yield useful information on the effectiveness of diabetes educators’ competencies on the diabetics’ self-management of the disease in Malaysia. The study will also describe the challenges faced by the Diabetes Educators in their daily task. This is a novel study and the result of the study can be generalized to the population of Diabetes Educators in Malaysia. The outcome of the study could facilitate the Training Division of Ministry of Health to review and enhance the implementation of the post-basic Diabetes Management course since there has not been any evaluation done after the course in the service site. Implication for practice and suggestions for further research will be discussed further.